Exploring the Perceived Value of an Open Digital Badge for Virtual Collaboration - Daniel Piedra (Canadian Society for Studies in Education, 2021)
Despite the recent growth in the development of alternative digital credentials within post-secondary education, students remain uncertain about their value and use. This article presents findings of a study conducted at McMaster University involving the implementation of an open digital badge to validate virtual collaboration within an experiential learning undergraduate-level course. The experience enabled students to demonstrate skills specific to talent acquisition within the human resources management diploma program while working collaboratively and virtually on an industry business project. Students who were successful in acquiring the virtual collaboration digital badge were surveyed both at the end of the course and 6-months following the completion of the course. The two questionnaires revealed that while the value of virtual collaboration as a skill-set was perceived as important, there is still uncertainty as to what an open digital badge is and how it can be of benefit to individuals.